An indium-zirconium bimetallic-porphyrin-ionic liquid multifunctionalized metal-organic framework catalyst

CN122999280APending Publication Date: 2026-10-30LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611144937.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

现有技术中,将IL嫁接到MOF上(IL@MOF)是常见策略,但仍存在显著不足:①Lewis酸性不足:多数IL@MOF依赖MOF本身的金属节点(如Zr4+、Zn2+)作为Lewis酸,其酸性强度有限,导致反应仍需较高温度或压力,或依赖外加共催化剂(如TBAB)来活化环氧环

Benefits of technology

1、创造了独特的“多功能协同”活性中心:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999280A_ABST
    Figure CN122999280A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of indium zirconium bimetallic-porphyrin-ionic liquid multifunctional metal organic framework catalyst, the chemical general formula of the catalyst is In x Zr 1‑x -MOF-(M)TCPP-IL;Wherein In x Zr 1‑x It indicates that zirconium oxygen cluster is basic node and part Zr 4+ It is replaced by In 3+ Isomorphous substitution bimetallic node, 0.05≤x≤0.4;MOF is the zirconium-based MOF skeleton based on terephthalic acid or its derivative;(M)TCPP indicates that four (4-carboxyl phenyl) metal (M) porphyrin unit is embedded in MOF skeleton by coordination bond or covalent bond, metal (M) is one of Fe, Co, Mn;-IL indicates that different chain length bromoalkyl imidazole bromide type ionic liquid unit is grafted on MOF skeleton by covalent bond.The catalyst described in the present application has the advantages of multiple functions and synergistic effect, ultra-high stability, can realize the high performance preparation cyclic carbonate of CO2 and epoxy in the absence of additional co-catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of heterogeneous catalytic materials, carbon dioxide resource utilization and green chemistry, and particularly to an indium zirconium bimetallic-porphyrin-ionic liquid multifunctional metal-organic framework catalyst. Background Technology

[0002] Converting the greenhouse gas carbon dioxide (CO2) into high-value-added cyclic carbonates is one of the important chemical pathways to achieve carbon neutrality. The key to this reaction lies in developing efficient, stable, and recyclable catalysts.

[0003] Metal-organic frameworks (MOFs) are considered ideal catalytic platforms due to their advantages such as designable structure, tunable porosity, and modifiable active sites. Ionic liquids (ILs) exhibit good activation and nucleophilic attack capabilities against CO2 and epoxides. In existing technologies, grafting ILs onto MOFs (IL@MOF) is a common strategy, but it still has significant shortcomings: ① Insufficient Lewis acidity: Most IL@MOFs rely on the metal nodes of the MOF itself (such as Zr). 4+ Zn 2+ As a Lewis acid, its acidity is limited, requiring higher temperatures or pressures for the reaction, or relying on external co-catalysts (such as TBAB) to activate the epoxy ring. ② Single or weak synergistic active sites: Existing functionalized MOFs are mostly single or bifunctional (such as metal + IL, or porphyrin + MOF), lacking multiple, highly effective synergistic active centers capable of simultaneously and efficiently activating the epoxy ring, adsorbing and activating CO2, and providing built-in nucleophiles. ③ Difficulty in balancing stability and activity: High activity often requires the introduction of unsaturated metal sites, which may sacrifice the stability of the MOF framework; on the other hand, highly stable MOFs (such as the UiO series) often lack sufficient inherent active sites. For example, the catalyst (Zn-MOF) used in published literature 1 (Cryst. Growth Des. 2022, 22, 598-607), although effective at room temperature and pressure, requires the addition of tetrabutylammonium bromide (TBAB) as a co-catalyst. The MOF catalyst (Bi-PCN-224) used in Published Reference 2 (ACS Catal. 2021, 11, 1988-1994) requires photoexcitation, limiting the reaction conditions. The (CoTCPP–UiO-66-IL) catalyst in Published Reference 3 (J.Environ. Chem.Eng., 2025, 13, 117062) achieved a yield of 99% under reaction conditions of 90℃, 0.1 MPa, and 12 h; however, the catalyst activity began to decline after two cycles. Published Reference 4 (In-IL MOF) showed that In... 3+While possessing the advantage of strong Lewis acidity, the catalyst cannot be recycled, and the yield of cyclic carbonates begins to decrease significantly from the second reaction, posing a serious challenge to the stability of the catalyst.

[0004] Therefore, developing a novel MOF catalyst that integrates strong Lewis acidity, multifunctional synergy, and ultra-high stability, and can achieve ultra-high catalytic performance under low pressure and medium-low temperature conditions without external co-catalysts, is a technical challenge that urgently needs to be overcome in this field. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to provide a multifunctional metal-organic framework catalyst with multiple functional synergistic effects and ultra-high stability, which is an indium-zirconium bimetallic-porphyrin-ionic liquid.

[0006] To address the aforementioned problems, the present invention provides an indium-zirconium bimetallic-porphyrin-ionic liquid multifunctional metal-organic framework catalyst, characterized in that: the catalyst has the general chemical formula In. x Zr 1-x -MOF-(M)TCPP-IL; where In x Zr 1-x This indicates that the basic nodes are zirconium-oxygen clusters and some Zr 4+ In 3+ The bimetallic nodes with isomorphous substitution, 0.05≤x≤0.4; MOF is a zirconium-based MOF framework based on terephthalic acid or its derivatives; (M)TCPP represents a tetra(4-carboxyphenyl)metal (M)porphyrin unit embedded in the MOF framework through coordination or covalent bonds, where metal (M) is one of Fe, Co, or Mn; -IL represents bromoalkylimidazolium bromide ionic liquid units of different chain lengths grafted onto the MOF framework through covalent bonds.

[0007] The MOF framework has a UiO-66, UiO-67 or MOF-808 topology.

[0008] The chemical formula of the (M)TCPP is ; In the formula: M is one of Fe, Co, and Mn.

[0009] The ionic liquid unit has a cation portion consisting of bromoalkylimidazolium cations of varying chain lengths, and an anion consisting of Br₂. - Its chemical formula is ; In the formula: n is 2 to 6.

[0010] The preparation method of the indium-zirconium bimetallic-porphyrin-ionic liquid multifunctional metal-organic framework catalyst described above is characterized by: dissolving zirconium salt, indium salt, terephthalic acid or its derivatives, and metal (M)porphyrin carboxylic acid in excess N,N-dimethylformamide (DMF), adding benzoic acid as a regulator, and after solvothermal reaction, washing and drying to obtain In. x Zr 1-x -MOF-(M)TCPP precursor; this precursor reacts with bromoalkylimidazolium bromide ionic liquids of different chain lengths under alkaline conditions at a molar ratio of (0.005:1) to (0.1:1), causing the ionic liquids to graft onto the framework. After washing and drying, the catalyst In is obtained. x Zr 1-x -MOF-(M)TCPP-IL.

[0011] The synthesis process is as follows: In the formula: M is one of Fe, Co, and Mn; x is the mole fraction of In, 0.05 ≤ x ≤ 0.4; n is 2~6.

[0012] The conditions for the solvothermal reaction are a temperature of 80~140 ℃ and a reaction time of 12~36 h.

[0013] The molar ratio of the zirconium salt to the indium salt is (2:1) to (19:1); the molar ratio of the zirconium salt to the terephthalic acid or its derivative is (5:1) to (1:2); the molar ratio of the zirconium salt to the metal (M)porphyrin carboxylic acid is (1:0.05) to (1:2); and the molar ratio of the zirconium salt to the benzoic acid is (1:0.05) to (1:0.2).

[0014] The alkaline conditions are provided by anhydrous potassium carbonate, and the reaction is carried out under nitrogen protection at 80~140 °C for 8~20 h; the molar ratio of anhydrous potassium carbonate to the precursor is (20:1)~(1:1).

[0015] The application of the indium-zirconium bimetallic-porphyrin-ionic liquid multifunctional metal-organic framework catalyst described above is characterized in that: under the condition of no external co-catalyst, the catalyst is used to catalyze the cycloaddition reaction of carbon dioxide with epoxide to prepare cyclic carbonates.

[0016] The reaction conditions refer to a carbon dioxide pressure of 0.1~2 MPa, a reaction temperature of 60~120 ℃, and a reaction time of 6~20 h.

[0017] The epoxide is selected from at least one of epichlorohydrin, propylene oxide, styrene oxide, 1,2-epoxyhexane, and 1,2-epoxycyclohexane.

[0018] Compared with the prior art, the present invention has the following advantages: 1. It created a unique "multifunctional synergistic" activity center: This invention is the first to utilize the strongly Lewis acidic In 3+ MTCPP, which combines Lewis acidity with electron transfer capabilities, and provides a strong nucleophilic bromide ion (Br₂) - Ionic liquids are precisely integrated into highly stable MOF single-phase materials through chemical bonds. 3+ The introduction of [a specific ingredient] significantly enhances the catalyst's intrinsic activation ability for the epoxy ring, which is beneficial for the ring-opening of the epoxy substrate.

[0019] 2. Excellent catalyst stability and recyclability: This invention uses UiO-type MOFs with extremely high chemical stability as the framework and introduces In through isomorphic substitution. 3+ It does not damage the main framework. The catalyst is a solid powder, which is easy to separate by centrifugation and can be reused at least 5 times while maintaining stable activity and structure.

[0020] 3. The synthesis method is controllable and has good reproducibility: This invention employs a stepwise post-synthesis grafting modification method. By adjusting the In / Zr ratio in the first step and the amount of ionic liquid grafting in the second step, the composition and performance of the catalyst can be precisely controlled. The process is stable and has scale-up potential.

[0021] 4. The catalyst described in this invention can be used to efficiently catalyze the cycloaddition reaction of carbon dioxide and epoxides under mild conditions without co-catalysts. Attached Figure Description

[0022] The specific embodiments of the present invention will be described in further detail below with reference to the accompanying drawings.

[0023] Figure 1 The Fourier transform infrared (FTIR) spectra of catalyst Cat-1 prepared in Example 1 and catalyst Cat-2 prepared in Example 2 of this invention.

[0024] Figure 2 This is a graph showing the conversion rate and recycling performance of catalyst Cat-1 in Example 5 of the present invention. Detailed Implementation

[0025] A multifunctional metal-organic framework catalyst based on indium-zirconium bimetallic-porphyrin-ionic liquid, the catalyst having the general chemical formula In x Zr 1-x-MOF-(M)TCPP-IL; where In x Zr 1-x This indicates that the zirconium oxide cluster ([Zr6O4(OH)4]) is the basic node and partially Zr 4+ In 3+ The bimetallic nodes with isomorphous substitution, 0.05≤x≤0.4; the MOF is a zirconium-based MOF framework based on terephthalic acid or its derivatives; (M)TCPP represents a tetra(4-carboxyphenyl)metal (M)porphyrin unit embedded in the MOF framework through coordination or covalent bonds, where the metal (M) is one of Fe, Co, or Mn; -IL represents bromoalkylimidazolium bromide ionic liquid units of different chain lengths grafted onto the MOF framework through covalent bonds (preferably ether or amide bonds).

[0026] Among them, the MOF framework has a UiO-66, UiO-67 or MOF-808 topology.

[0027] The chemical formula of (M)TCPP is ; In the formula: M is one of Fe, Co, and Mn.

[0028] The cation portion of the ionic liquid unit is a bromoalkylimidazolium cation of varying chain lengths, with the alkyl chain being a C2-C6 straight-chain alkyl group, more preferably butyl (Bu), and the anion being Br. - Its chemical formula is ; In the formula: n is 2 to 6.

[0029] The catalyst was prepared using a post-grafting method, the specific process of which is as follows: Zirconium salt, indium salt, terephthalic acid or its derivatives, and metal (M)porphyrin carboxylic acid (MTCPP) were dissolved in excess N,N-dimethylformamide (DMF), with benzoic acid added as a regulator. The mixture was subjected to a solvothermal reaction at 80–140 °C for 12–36 h. After washing and drying, In was obtained. x Zr 1-x -MOF-(M)TCPP precursor. The molar ratio of zirconium salt to indium salt is (2:1) to (19:1); the molar ratio of zirconium salt to terephthalic acid or its derivative is (5:1) to (1:2); the molar ratio of zirconium salt to metal (M)porphyrin carboxylic acid is (1:0.05) to (1:2); the molar ratio of zirconium salt to benzoic acid is (1:0.05) to (1:0.2). 2,5-Dihydroxyterephthalic acid or its derivative is preferred.

[0030] The precursor reacts with bromoalkylimidazolium bromide ionic liquids of different chain lengths at a molar ratio of (0.005:1) to (0.1:1) under alkaline conditions, allowing the ionic liquids to covalently graft onto the phenolic hydroxyl groups of the MOF backbone. The alkaline conditions are provided by anhydrous potassium carbonate, and the reaction is carried out under nitrogen protection at 80–140 °C for 8–20 h; the molar ratio of anhydrous potassium carbonate to the precursor is (20:1) to (1:1). After the reaction, the product is washed and dried to obtain the catalyst In. x Zr 1-x -MOF-(M)TCPP-IL.

[0031] The application of this catalyst refers to its use in the cycloaddition reaction of carbon dioxide with epoxide to prepare cyclic carbonates under conditions without external co-catalysts. The carbon dioxide pressure is 0.1~2 MPa, the reaction temperature is 60~120℃, and the reaction time is 6~20h.

[0032] Wherein: the epoxide is selected from at least one of epichlorohydrin, propylene oxide, styrene oxide, 1,2-epoxyhexane and 1,2-epoxycyclohexane.

[0033] Example 1: In 0.1 Zr 0.9 Preparation of -UiO-66-CoTCPP-IL(BuImBr) S1 precursor In 0.1 Zr 0.9 Synthesis of -UiO-66-CoTCPP: ZrCl4 (0.72 mmol, 168.0 mg), InCl3 (0.08 mmol, 17.6 mg), 2,5-dihydroxyterephthalic acid (DHTA, 0.20 mmol, 39.6 mg), tetrakis(4-carboxyphenyl)cobalt porphyrin (CoTCPP, 0.04 mmol, approximately 34 mg), and benzoic acid (8.0 mmol, 976 mg) were dissolved in 40 mL of anhydrous DMF and sonicated for 30 minutes to ensure uniform dispersion. The mixture was transferred to a 100 mL high-pressure reactor lined with polytetrafluoroethylene and reacted in an oven at 120 °C for 24 hours. After natural cooling, the solid was collected by centrifugation, washed three times each with DMF and methanol, and finally dried under vacuum at 120 °C for 12 hours to obtain a dark purple powder, designated as precursor-1.

[0034] S2 ionic liquid grafting: In a 50 mL round-bottom flask equipped with a condenser, the above-mentioned precursor-1 (80 mg), anhydrous K₂CO₃ (56 mg), 4-bromobutyl-2-methylimidazolium bromide (BuImBr, 1.27 g), and anhydrous DMF (10 mL) were added. Under nitrogen protection, the mixture was heated to 120 °C and stirred under reflux for 12 hours. After the reaction was completed, the mixture was cooled to room temperature, centrifuged to collect the solid, washed three times each with ethanol and acetone, and dried under vacuum at 90 °C for 12 hours to obtain the final catalyst, denoted as Cat-1.

[0035] Fourier transform infrared spectroscopy was performed on catalyst Cat-1, and the results are as follows: Figure 1 As shown in the figure. It can be seen from the figure that ~1000cm -1 The characteristic peaks in the vicinity, belonging to Co-N, are located at 1400–1500 cm⁻¹. -1 Characteristic peaks attributable to the porphyrin ring, 1600–1700 cm⁻¹ -1 The characteristic peaks belonging to C=O indicate that the catalyst contains structural units of UiO-66 and Co-TCPP, and the target catalyst Cat-1 was successfully synthesized.

[0036] Example 2: In 0.1 Zr 0.9 Preparation of -UiO-66-FeTCPP-IL(BuImBr) S1 precursor In 0.2 Zr 0.8 Synthesis of -UiO-66-FeTCPP: ZrCl4 (0.64 mmol, 149.2 mg), InCl3 (0.16 mmol, 35.2 mg), 2,5-dihydroxyterephthalic acid (DHTA, 0.80 mmol, 160 mg), tetrakis(4-carboxyphenyl)cobalt porphyrin (FeTCPP, 0.04 mmol, approximately 34 mg), and benzoic acid (5.0 mmol, 976 mg) were dissolved in 40 mL of anhydrous DMF and sonicated for 30 minutes to ensure uniform dispersion. The mixture was transferred to a 100 mL high-pressure reactor lined with polytetrafluoroethylene and reacted in an oven at 120 °C for 24 hours. After natural cooling, the solid was collected by centrifugation, washed three times each with DMF and methanol, and finally dried under vacuum at 120 °C for 12 hours to obtain a dark purple powder, designated as precursor-2.

[0037] S2 ionic liquid grafting: In a 50 mL round-bottom flask equipped with a condenser, the above-mentioned precursor-2 (40 mg), anhydrous K₂CO₃ (28 mg), 4-bromobutyl-2-methylimidazolium bromide (BuImBr, 1.27 g), and anhydrous DMF (5 mL) were added. Under nitrogen protection, the mixture was heated to 120 °C and stirred under reflux for 12 hours. After the reaction was completed, the mixture was cooled to room temperature, centrifuged to collect the solid, washed three times each with ethanol and acetone, and dried under vacuum at 100 °C for 12 hours to obtain the final catalyst, denoted as Cat-2.

[0038] Fourier transform infrared spectroscopy was performed on catalyst Cat-2, and the results are as follows: Figure 1 As shown in the figure. It can be seen from the figure that it exists at 750 cm. -1 The CN characteristic peak, attributed to ionic liquids, is located at 1400–1500 cm⁻¹. -1 Characteristic peaks attributable to the porphyrin ring, 1600–1700 cm⁻¹ -1 The characteristic peaks attributed to C=O indicate successful grafting of the 4-bromobutyl-2-methylimidazolium bromide ionic liquid onto In. 0.2 Zr 0.8 The target catalyst Cat-2 was synthesized on the surface of the UiO-66-CoTCPP MOF catalyst precursor.

[0039] Example 3: In 0.1 Zr 0.9 Preparation of -UiO-66-CoTCPP-IL(MImBr) S1 precursor In 0.3 Zr 0.7 Synthesis of -UiO-66-CoTCPP: ZrCl4 (0.56 mmol, 131.0 mg), InCl3 (0.12 mmol, 26.4 mg), 2,5-dihydroxyterephthalic acid (DHTA, 0.80 mmol, 160.4 mg), tetrakis(4-carboxyphenyl)cobalt porphyrin (CoTCPP, 0.04 mmol, approximately 34 mg), and benzoic acid (8.0 mmol, 976 mg) were dissolved in 40 mL of anhydrous DMF and sonicated for 30 minutes to ensure uniform dispersion. The mixture was transferred to a 100 mL high-pressure reactor lined with polytetrafluoroethylene and reacted in an oven at 140 °C for 24 hours. After natural cooling, the solid was collected by centrifugation, washed three times each with DMF and methanol, and finally dried under vacuum at 120 °C for 20 hours to obtain a dark purple powder, designated as precursor-3.

[0040] S2 ionic liquid grafting: In a 50 mL round-bottom flask equipped with a condenser, the above-mentioned precursor-3 (40 mg), anhydrous K₂CO₃ (28 mg), 4-bromobutyl-2-methylimidazolium bromide (MImBr, 1.12 g), and anhydrous DMF (5 mL) were added. Under nitrogen protection, the mixture was heated to 120 °C and stirred under reflux for 12 hours. After the reaction was completed, the mixture was cooled to room temperature, centrifuged to collect the solid, washed three times each with ethanol and acetone, and dried under vacuum at 100 °C for 12 hours to obtain the final catalyst, denoted as Cat-3.

[0041] Example 4: In 0.1 Zr 0.9 Preparation of -UiO-66-CoTCPP-IL(EtImBr) S1 precursor In 0.1 Zr 0.9 Synthesis of -UiO-66-CoTCPP: ZrCl4 (0.18 mmol, 42.0 mg), InCl3 (0.02 mmol, 4.4 mg), 2,5-dihydroxyterephthalic acid (DHTA, 0.20 mmol, 39.6 mg), tetrakis(4-carboxyphenyl)cobalt porphyrin (CoTCPP, 0.01 mmol, approximately 8.5 mg), and benzoic acid (2.0 mmol, 244 mg) were dissolved in 10 mL of anhydrous DMF and sonicated for 30 minutes to ensure uniform dispersion. The mixture was transferred to a 100 mL polytetrafluoroethylene-lined autoclave and reacted in an oven at 120 °C for 24 hours. After natural cooling, the solid was collected by centrifugation, washed three times each with DMF and methanol, and finally dried under vacuum at 120 °C for 12 hours to obtain a dark purple powder, designated as precursor-4.

[0042] S2 ionic liquid grafting: In a 50 mL round-bottom flask equipped with a condenser, the above-mentioned precursor-4 (40 mg), anhydrous K₂CO₃ (28 mg), 2-bromo-ethyl-2-methylimidazolium bromide (EtImBr, 1.37 g), and anhydrous DMF (5 mL) were added. Under nitrogen protection, the mixture was heated to 120 °C and stirred under reflux for 12 hours. After the reaction was completed, the mixture was cooled to room temperature, centrifuged to collect the solid, washed three times each with ethanol and acetone, and dried under vacuum at 100 °C for 12 hours to obtain the final catalyst, denoted as Cat-4.

[0043] Example 5 In a 50 mL Schneider flask, 5 mmol of epichlorohydrin (ECH) and 20 mg of the Cat-1 catalyst prepared in Example 1 were added (the catalyst molar fraction was approximately 0.6% based on the total metal content). The flask was then filled with 0.1 MPa CO2 and sealed. It was placed in a 90°C oil bath and magnetically stirred. After reacting for 10 hours, the mixture was cooled in an ice-water bath, and the catalyst was separated by centrifugation. The supernatant was collected, and the product 4-(chloromethyl)-1,3-dioxolane-2-one (CPC) was quantitatively analyzed by gas chromatography to be 4.96 mmol. The ECH conversion was calculated to be 100%, and the CPC selectivity was >99%.

[0044] The recyclability of catalyst Cat-1 was investigated, and the results are as follows: Figure 2 As shown in the figure, the conversion rate of ECH and the selectivity of CPC remain basically unchanged after the catalyst is used 4 times, indicating that the Cat-1 catalyst has good recycling performance.

[0045] Example 6 In a 50 mL Schneider flask, 5 mmol of epichlorohydrin (ECH) and 20 mg of the Cat-2 catalyst prepared in Example 2 (the catalyst molar fraction was approximately 1.0% based on the total metal content) were added. The flask was then filled with 0.1 MPa CO2 and sealed. It was placed in a 100°C oil bath and magnetically stirred. After reacting for 10 hours, the mixture was cooled in an ice-water bath, and the catalyst was separated by centrifugation. The supernatant was collected, and the product 4-(chloromethyl)-1,3-dioxolane-2-one (CPC) was quantitatively analyzed by gas chromatography to be 4.91 mmol. The ECH conversion was calculated to be 100%, and the CPC selectivity was >98%.

[0046] Example 7 In a 50 mL Schneider flask, 5 mmol of epichlorohydrin (ECH) and 20 mg of the Cat-3 catalyst prepared in Example 3 (the catalyst molar fraction was approximately 0.8% based on the total metal content) were added. The flask was then filled with 0.1 MPa CO2 and sealed. It was placed in a 100°C oil bath and magnetically stirred. After reacting for 10 hours, the mixture was cooled in an ice-water bath, and the catalyst was separated by centrifugation. The supernatant was collected, and the product 4-(chloromethyl)-1,3-dioxolane-2-one (CPC) was quantitatively analyzed by gas chromatography to be 4.60 mmol. The calculated ECH conversion was 92%, and the CPC selectivity was >99%.

[0047] Example 8 In a 50 mL Schneider flask, 5 mmol of epichlorohydrin (ECH) and 20 mg of the Cat-4 catalyst prepared in Example 4 were added (the catalyst molar fraction was approximately 0.6% based on the total metal content). The flask was then filled with 0.1 MPa CO2 and sealed. It was placed in a 90°C oil bath and magnetically stirred. After reacting for 10 hours, the mixture was cooled in an ice-water bath, and the catalyst was separated by centrifugation. The supernatant was collected, and the product 4-(chloromethyl)-1,3-dioxolane-2-one (CPC) was quantitatively analyzed by gas chromatography to be 4.97 mmol. The calculated ECH conversion was 99%, and the CPC selectivity was >99%.

[0048] Example 9 In a 50 mL Schneider flask, 5 mmol of propylene oxide (PO) and 20 mg of the Cat-1 catalyst prepared in Example 1 (the catalyst molar fraction was approximately 0.4% based on the total metal content) were added. The flask was then sealed with 0.1 MPa CO2. It was placed in a 100°C oil bath and magnetically stirred. After reacting for 10 hours, the mixture was cooled in an ice-water bath, and the catalyst was separated by centrifugation. The supernatant was collected, and the product propylene carbonate (PC) was quantitatively analyzed by gas chromatography to be 4.96 mmol. The calculated PO conversion was 99%, and the PC selectivity was >99%.

[0049] Example 10 In a 50 mL Schneider flask, 5 mmol of propylene oxide (PO) and 20 mg of the Cat-2 catalyst prepared in Example 2 (the catalyst molar fraction was approximately 0.4% based on the total metal content) were added. The air was replaced three times with CO2, and the flask was then filled with 0.1 MPa CO2 and sealed. The flask was placed in a 90°C oil bath and magnetically stirred. After reacting for 10 hours, the mixture was cooled in an ice-water bath, and the catalyst was separated by centrifugation. The supernatant was collected, and the product propylene carbonate (PC) was quantitatively analyzed by gas chromatography to be 4.86 mmol. The calculated PO conversion was 97%, and the PC selectivity was >99%.

[0050] Example 11 In a 50 mL Schneider flask, 5 mmol of propylene oxide (PO) and 20 mg of the Cat-3 catalyst prepared in Example 3 were added (the catalyst molar fraction was approximately 0.5% based on the total metal content). The air was replaced three times with CO2, and the flask was then filled with 0.1 MPa CO2 and sealed. The flask was placed in a 90°C oil bath and magnetically stirred. After reacting for 10 hours, the mixture was cooled in an ice-water bath, and the catalyst was separated by centrifugation. The supernatant was collected, and the product propylene carbonate (PC) was quantitatively analyzed by gas chromatography to be 4.71 mmol. The calculated PO conversion was 94%, and the PC selectivity was >99%.

[0051] Example 12 In a 50 mL Schneider flask, 5 mmol of styrene oxide (StO) and 20 mg of the Cat-4 catalyst prepared in Example 2 were added (the catalyst molar fraction was approximately 1.5% based on the total metal content). The air was replaced three times with CO2, and the flask was then filled with 0.1 MPa CO2 and sealed. The flask was placed in a 100°C oil bath and magnetically stirred. After reacting for 10 hours, the mixture was cooled in an ice-water bath, and the catalyst was separated by centrifugation. The supernatant was collected, and the product styrene carbonate (StC) was quantitatively analyzed by gas chromatography to be 4.75 mmol. The calculated conversion of StO was 98%, and the selectivity of StC was >97%.

Claims

1. A multifunctional metal-organic framework catalyst based on indium-zirconium bimetallic-porphyrin-ionic liquid, characterized in that: The general chemical formula of this catalyst is In x Zr 1-x -MOF-(M)TCPP-IL; where In x Zr 1-x This indicates that the basic nodes are zirconium-oxygen clusters and some Zr 4+ In 3+ The bimetallic nodes with isomorphous substitution, 0.05≤x≤0.4; MOF is a zirconium-based MOF framework based on terephthalic acid or its derivatives; (M)TCPP represents a tetra(4-carboxyphenyl)metal (M)porphyrin unit embedded in the MOF framework through coordination or covalent bonds, where metal (M) is one of Fe, Co, or Mn; -IL represents bromoalkylimidazolium bromide ionic liquid units of different chain lengths grafted onto the MOF framework through covalent bonds.

2. The indium-zirconium bimetallic-porphyrin-ionic liquid multifunctional metal-organic framework catalyst as described in claim 1, characterized in that: The MOF framework has a UiO-66, UiO-67 or MOF-808 topology.

3. The indium-zirconium bimetallic-porphyrin-ionic liquid multifunctional metal-organic framework catalyst as described in claim 1, characterized in that: The chemical formula of the (M)TCPP is ; In the formula: M is one of Fe, Co, and Mn.

4. The indium-zirconium bimetallic-porphyrin-ionic liquid multifunctional metal-organic framework catalyst as described in claim 1, characterized in that: The ionic liquid unit has a cation portion consisting of bromoalkylimidazolium cations of varying chain lengths, and an anion consisting of Br₂. - Its chemical formula is ; In the formula: n is 2 to 6.

5. The preparation method of the indium-zirconium bimetallic-porphyrin-ionic liquid multifunctional metal-organic framework catalyst as described in claim 1, characterized in that: Zirconium salt, indium salt, terephthalic acid or its derivatives, and metal (M) porphyrin carboxylic acid are dissolved in excess N,N-dimethylformamide, and benzoic acid is added as a regulator. After solvothermal reaction, the mixture is washed and dried to obtain In. x Zr 1-x -MOF-(M)TCPP precursor; this precursor reacts with bromoalkylimidazolium bromide ionic liquids of different chain lengths under alkaline conditions at a molar ratio of (0.005:1) to (0.1:1), causing the ionic liquids to graft onto the framework. After washing and drying, the catalyst In is obtained. x Zr 1-x -MOF-(M)TCPP-IL.

6. The preparation method of the indium-zirconium bimetallic-porphyrin-ionic liquid multifunctional metal-organic framework catalyst as described in claim 5, characterized in that: The conditions for the solvothermal reaction are a temperature of 80~140 ℃ and a reaction time of 12~36 h.

7. The preparation method of the indium-zirconium bimetallic-porphyrin-ionic liquid multifunctional metal-organic framework catalyst as described in claim 5, characterized in that: The molar ratio of the zirconium salt to the indium salt is (2:1) to (19:1); the molar ratio of the zirconium salt to the terephthalic acid or its derivative is (5:1) to (1:2); the molar ratio of the zirconium salt to the metal (M)porphyrin carboxylic acid is (1:0.05) to (1:2); and the molar ratio of the zirconium salt to the benzoic acid is (1:0.05) to (1:0.2).

8. The preparation method of the indium-zirconium bimetallic-porphyrin-ionic liquid multifunctional metal-organic framework catalyst as described in claim 5, characterized in that: The alkaline conditions are provided by anhydrous potassium carbonate, and the reaction is carried out under nitrogen protection at 80~140℃ for 8~20 h; the molar ratio of anhydrous potassium carbonate to the precursor is (20:1)~(1:1).

9. The application of the indium-zirconium bimetallic-porphyrin-ionic liquid multifunctional metal-organic framework catalyst as described in claim 1, characterized in that: This catalyst, without the addition of an external co-catalyst, is used in the cycloaddition reaction of carbon dioxide with epoxides to prepare cyclic carbonates.

10. The application of the indium-zirconium bimetallic-porphyrin-ionic liquid multifunctional metal-organic framework catalyst as described in claim 9, characterized in that: The reaction conditions refer to a carbon dioxide pressure of 0.1~2 MPa, a reaction temperature of 60~120 ℃, and a reaction time of 6~20 h.

11. The application of the indium-zirconium bimetallic-porphyrin-ionic liquid multifunctional metal-organic framework catalyst as described in claim 9, characterized in that: The epoxide is selected from at least one of epichlorohydrin, propylene oxide, styrene oxide, 1,2-epoxyhexane, and 1,2-epoxycyclohexane.